353 Jeavons syndrome-a photosensitive epilepsy syndrome. (17th August 2022) - Kuriakose, Mathews E; Zacharias, Rekha; Athira, R
Abstract : Aims: Jeavons syndrome refers to a rare form of generalized epilepsy which is characterized by specific clinical features like eyelid myoclonia, photosensitivity and EEG changes. Here we report the case of an adolescent girl who presented as a case of status epilepticus, though a detailed history taking with high index of suspicion could help us in arriving at the diagnosis of a rare photosensitive epileptic syndrome. Methods: A 12 year old adolescent female without significant medical history presented to casualty as a referred case with history of two distinct episodes of status epilepticus. Her CNS examination was within normal limits. On detailed history taking mother gave a history of multiple episodes of jerky movement of eyes followed by vacant, lasting for few seconds which was noted from the age of 3 ½ years, but treated as nil significant. Blood investigation and MRI was normal. However, EEG was abnormal with generalized spike and wave epileptic activity with eye closure sensitivity ( figure 1 ) diagnostic of Jeavons syndrome (JS). Results: JS is characterized by eyelid myoclonia, eye closure induced seizure and photosensitivity3.The eye movements are rhythmic, single, or multiple, slight or marked even in the same patient. These movements are under voluntary, automatic, reflex autonomic and emotional control1. Eyelid myoclonia may be followed or not by brief absences lasting for less than 6 seconds. Seizure occurs mainly following eye closure, multiple times per day and may progress to GCTS and status epilepticus4. Precipitating factors include sleep deprivation, alcohol abuse, poor drug tolerance, bright light sensitivity, television or video game exposure. Photosensitivity is deceased as age advances and diminished with antiepileptic agents. The occipital visual cortex may play a vital role in JS.The intensity of light alters the area of activation in occipital cortex, leading to activation of epileptogenic cortex and or the excitability. Generalized or predominantly frontorolandic paroxysmal discharges occurs as a part of spreading of visual response to the occipital cortex via transcortical or thalamocortical interactions. Reciprocal interaction of thalamocortical pathways is essential in generating rhythemic spike and wave (and absence) following initial polyspike and myoclonic discharges. In addition, brainstem also plays a pivotal role in generating photomyoclonic response3. Anti epileptic choice includes levetiracetam, sodium valproate, lamotrigine and ethosuximide, though drug resistance is not uncommon. It is also seen to respond to ketogenic diet2. Differential diagnosis includes conditions with eye closure sensitivity like juvenile absence epilepsy, juvenile myoclonic epilepsy idiopathic occipital lobe epilepsy. Childhood absence epilepsy, juvenile absence epilepsy and sunflower syndromes are some epileptic syndromes associated with eyelid myoclonia. Photosensitive seizures includes benign myoclonic epilepsy of infancy, idiopathic generalized epilepsy with tonic clonic seizues and Dravets syndrome. Conclusion: Jeavons syndrome is an underdiagnosed or misdiagnosed idiopathic photosensitive epilepsy syndrome with characteristic eyelid myoclonia and absence with female preponderance and familial clustering. It has childhood onset with good response to anti-epileptic drugs. Diagnosis can be made by typical clinical features with specific EEG changes. Studies reveals the possibility of the occipital cortex initiating the generalized epilepsy network including thalamocortical and transcortical pathways and brain stem.